-8+6(c+2)=-21

Simple and best practice solution for -8+6(c+2)=-21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8+6(c+2)=-21 equation:


Simplifying
-8 + 6(c + 2) = -21

Reorder the terms:
-8 + 6(2 + c) = -21
-8 + (2 * 6 + c * 6) = -21
-8 + (12 + 6c) = -21

Combine like terms: -8 + 12 = 4
4 + 6c = -21

Solving
4 + 6c = -21

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 6c = -21 + -4

Combine like terms: 4 + -4 = 0
0 + 6c = -21 + -4
6c = -21 + -4

Combine like terms: -21 + -4 = -25
6c = -25

Divide each side by '6'.
c = -4.166666667

Simplifying
c = -4.166666667

See similar equations:

| 9x=81(x+3) | | 2(8x^2-25x-28)= | | -8+6x+3x=64 | | 5m-3Q=2+w(4Q-7m)forQ | | 9x-6(3-x)=3(x+6) | | 16=7(a-3)-12 | | -35=-5(m-3) | | 4x^2-18x+19=0 | | 1+5e+2e=78 | | 8x+2(x-4)=3(x+1)-2 | | -6(a-3)=24 | | 3x+5=3(x+3) | | 20=-16t(t-3) | | -3x-5(-x-4)=2 | | -5(y+2)=10 | | -1-7x+6x=-1 | | 4x+6y=103x+7y=12.5 | | 6(7x-1)=42x-6 | | 5(x+2)=-7x | | sqrt(-6y+37)=y-5 | | z=20x+6y | | 4y+9=z | | 3n-5=3n | | (3x^2-20x-7)=0 | | -3x-4x-6=-61 | | sin(x)=0.8191 | | 37=-7x+2(5x+2) | | 3log(4x)2=10 | | x^4+x^3+4x^2-24x-72=0factor | | x^4+x^3+4x^2-24x-72=0 | | factorx^4+x^3+4x^2-24x-72=0 | | 3(2x+5)+14=4(3x-7)-3 |

Equations solver categories